2004
DOI: 10.1097/00129039-200403000-00003
|View full text |Cite
|
Sign up to set email alerts
|

HER-2/neu (c-erbB-2) Evaluation in Primary Breast Carcinoma by Fluorescent In Situ Hybridization and Immunohistochemistry With Special Focus on Intratumor Heterogeneity and Comparison of Invasive and In Situ Components

Abstract: We have studied the intratumor HER-2/neu heterogeneity in 78 consecutive and population-based primary invasive breast carcinomas. Within the invasive component, heterogeneity was detected in only 1 of 78 tumors. In 48 tumors (62%), we found both in situ and invasive components in analyzed tissue sections. Twelve of these 48 tumors had a difference of at least 2 arbitrary units in the in situ compared with the invasive part of the tumor with regard to the HER-2/neu status analyzed by HercepTest (immunohistochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 33 publications
2
17
0
1
Order By: Relevance
“…In some cases, diverse gene copy aberrations were found 18 . Intra-tumor heterogeneity also has been observed in breast cancer biomarkers (ER, PR, HER2), where tumors with spatial areas will exhibit high or low expression of these biomarkers [54][55][56][57][58] .…”
Section: Cancer Stem Cell Theorymentioning
confidence: 97%
“…In some cases, diverse gene copy aberrations were found 18 . Intra-tumor heterogeneity also has been observed in breast cancer biomarkers (ER, PR, HER2), where tumors with spatial areas will exhibit high or low expression of these biomarkers [54][55][56][57][58] .…”
Section: Cancer Stem Cell Theorymentioning
confidence: 97%
“…RTKs are transmembrane proteins that serve as receptors for many growth factors, and activation of the RTK signaling pathways lead to cell proliferation and anti-apoptotic activity. Heterogeneous expression of RTKs in cancer cells has also been reported (Andersson et al 2004). Taken together, determination of the expression heterogeneity of these biomarkers would be required for the identification of clinically relevant biomarkers.…”
Section: Introductionmentioning
confidence: 93%
“…8,13,14 Intratumoral heterogeneity of HER2 gene amplification has been demonstrated in a subset of breast cancers. [15][16][17][18][19][20][21][22][23] However, as the previous studies targeted different sets of samples, the frequency of intratumoral HER2 heterogeneity was quite variable and was not comparable between the studies. Andersson et al 15 found HER2 heterogeneity within the invasive components of breast cancers in only 1 of 78 tumors.…”
mentioning
confidence: 99%